Clinical evaluation of periodontal status in subjects with multibracket appliances and the role of age and gender during initial months of fixed orthodontic treatment - Sapna Singla; Monika Kamboj; Priyanka Gupta; Gurvanit Lehl; Manjit Talwar (Wolters Kluwer Medknow Publications, 2022)
Background: During fixed orthodontic treatment, the presence of various fixed appliances like brackets in the oral cavity for a long period leads to various changes in the oral microflora, ultimately affecting the periodontal health of the teeth. Hence, the current study was performed to clinically assess the periodontal status of the subjects undergoing fixed orthodontic treatment and to evaluate the role of age and gender during the first 6 months of treatment. Materials and Methods: Forty-one subjects (26 females and 15 males) in the age range of 12-28 years scheduled for fixed orthodontic treatment were included in the study. Twenty-eight subjects were adolescents with a mean age of 13.96 years and 13 were adults with a mean age of 22.38 years. Plaque index (PI) and gingival index (GI) were recorded at the beginning and the end of 1, 2, 3, and 6 months of the treatment, and pocket probing depth (PPD) was evaluated at the start and after 6 months of fixed orthodontic treatment. Results: The study showed a statistically significant increase in the mean values of PI (1.10 ± 0.264) and GI (0.929 ± 0.220) over a period of 6 months when compared with the baseline mean values, i.e., 0.557 ± 0.224 and 0.423 ± 0.329, respectively (P < 0.001). The mean PPD values exhibited no significant change. Effect of orthodontic treatment on adolescents/adults and between genders did not statistically differ. Conclusions: Fixed orthodontic treatment with multibracket appliances significantly increases plaque accumulation leading to significant inflammatory changes in the gingival tissues without any significant changes in the clinical probing depths of the pockets regardless of age and gender.